Numerical Investigation of the Effects of Flexible Joint Connection Details on the In-Plane Behavior of Reinforced Concrete Frames - Altıok, Taha Yasin (Fırat University, 2025)
Infill walls quickly become damaged under in-plane and out-of-plane effects, losing their effectiveness within the structural system. Therefore, in recent years, researchers have focused on alternative connection details to better understand the effects of infill walls on the structural system and to minimize the negative effects caused by these elements. This study aimed to numerically investigate the flexible joint connection detail recommended in the Türkiye Building Earthquake Code-2018 (TBEC-2018), focusing on in-plane behavior. This detail was intended to prevent damage to infill walls at low interstory drift levels and to mitigate their negative effects on the structural system. In this context, a total of four reinforced concrete frame models were created: one without walls (BF), one with rigid connections (IF-R), and two with flexible joint connections of varying thicknesses (IF-F30 and IF-F60). Their performance was evaluated under repeated and reversible lateral loads using nonlinear Dynamic/Implicit (Quasi-Static) analyses. The findings indicate that flexible joint connections delay plastic deformation by more evenly distributing stress and damage, while maintaining the system's load-bearing capacity even with large interstory drifts. Furthermore, increasing the flexible joint thickness was found to positively impact ductility and provide more stable and balanced behavior compared to rigid infill connections. These results demonstrate that considering flexible joint details in the structural design process can significantly contribute to performance.

Dolgu duvarlar, düzlem içi ve düzlem dışı etkiler altında kısa sürede hasar alarak yapısal sistem içerisindeki etkinliklerini kaybetmektedir. Bu nedenle, son yıllarda araştırmacılar, dolgu duvarların yapısal sistem üzerindeki etkilerini daha iyi anlamak ve bu elemanların sebep olduğu olumsuzlukları minimize edebilmek amacıyla alternatif bağlantı detaylarına odaklanmıştır. Bu çalışma, Türkiye Bina Deprem Yönetmeliği-2018 (TBDY-2018)’de önerilen esnek derz bağlantı detayını, özellikle düzlem içi davranış açısından sayısal olarak incelemeyi amaçlamaktadır. Bu detayın, düşük göreli kat ötelemesi seviyelerinde dolgu duvarlarının hasar görmesini önlemesi ve yapısal sistem üzerindeki olumsuz etkilerini azaltması hedeflenmektedir. Bu kapsamda, biri duvarsız (BF), biri rijit bağlı (IF-R) ve ikisi farklı kalınlıkta esnek derz bağlantılı (IF-F30 ve IF-F60) olmak üzere toplam dört betonarme çerçeve modeli oluşturulmuş; doğrusal olmayan Dynamic/Implicit (Quasi-Static) analizlerle tekrarlı ve tersinir yatay yükler altında performansları değerlendirilmiştir. Elde edilen bulgular, esnek derz bağlantılarının gerilme ve hasar dağılımını daha yayılı hale getirerek plastik şekil değiştirmeyi geciktirdiğini ve büyük göreli kat ötelemelerinde dahi sistemin taşıma kapasitesini koruduğunu göstermektedir. Ayrıca, esnek derz kalınlığının artırılmasının sünekliği olumlu etkilediği ve rijit dolgu bağlantısına kıyasla daha kararlı ve dengeli bir davranış sağladığı görülmüştür. Bu sonuçlar, esnek derz detaylarının yapısal tasarım sürecinde dikkate alınmasının, performans açısından önemli katkılar sunabileceğini ortaya koymaktadır.
Esnek Derz Bağlantı Detaylarının Betonarme Çerçevelerin Düzlem İçi Davranışına Etkisinin Nümerik Olarak İncelenmesi
Keywords: Civil Engineering (Other); İnşaat Mühendisliği (Diğer)